BEYOND VIRALITY: A STUDY OF INDONESIAâS VIRAL VIDEO ADS - Fauzan Alyafie, Muhammad
With a strong interest from both customers and companies in a more dynamic type of advertisement and content, brands are now focusing on creating video advertisements that hopefully will be viewed by many consumers and shared contagiously. However, being “viral” does not necessarily boost brand-related outcomes, which is what a company eventually needs. They need to go beyond mere virality. Brands need to find a valuable virality which not only focuses on the number of shares but also the effect on brand evaluation and the number of purchases. Using a collection of Indonesia’s most popular video ads curated by YouTube Indonesia, the study was able to examine how emotional combinations in ads can affect valuable virality. The results indicate that there are two emotional combinations among Indonesia’s viral ads, one that focuses strongly on the emotion of joy and surprise (positive ads) and another that has more complex and contrasting emotions of sadness paired with joy (mixed ads). An experiment by giving different types of ads into two different groups of a single population further demonstrates how a different type of ads can create a different effect on valuable virality. Mixed ads with a more complex emotion edge out positive ads in terms of brand-related outcomes. As for the sharing intention, there is no difference between what positive and mixed ads can do. The findings shed light on Indonesia’s viral video ads current landscape and how companies can create an emotional combination in their video ads which maximizes their objectives.